2017
DOI: 10.1111/1460-6984.12339
|View full text |Cite
|
Sign up to set email alerts
|

More or less likely to offend? Young adults with a history of identified developmental language disorders*

Abstract: BackgroundThere is now substantial literature demonstrating that a disproportionate number of young people who come into contact with youth justice services evidence unidentified language difficulties. These young people, therefore, have received little or no professional input in this area. Conversely, there is a dearth of research pertaining to criminality outcomes among those individuals with identified developmental language disorders (DLD) who have received such interventions.AimsTo examine police‐initiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 85 publications
(153 reference statements)
3
37
0
4
Order By: Relevance
“…It is encouraging that young adults with DLD do not report markedly different reading behaviour from their peers. There have been recent arguments made about the potential beneficial distal effects of early identification and intervention like that received by participants in the MLS (Winstanley et al 2018). The vast majority of adults with DLD does read from internet sources; however, a small minority are never accessing this material.…”
Section: Discussionmentioning
confidence: 99%
“…It is encouraging that young adults with DLD do not report markedly different reading behaviour from their peers. There have been recent arguments made about the potential beneficial distal effects of early identification and intervention like that received by participants in the MLS (Winstanley et al 2018). The vast majority of adults with DLD does read from internet sources; however, a small minority are never accessing this material.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with identification strategy employed by Winstanley et al . (2018) (Winstanley et al . 2018) in an age matched study of young adults with a history of identified language disorders.…”
Section: Methodsmentioning
confidence: 99%
“…A second strand of literature relevant to this study has focused on individuals in youth justice, as these individuals present with very high rates of SLCN and potentially very high costs (Snow 2013, Snow and Powell 2004, Winstanley et al . 2018). A UK study by Winstanley et al .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations